Primary ciliary dyskinesia with normal ultrastructure: three-dimensional tomography detects absence of DNAH11. Issue 2 (22nd February 2018) - Shoemark, Amelia; Burgoyne, Thomas; Kwan, Robert; Dixon, Mellisa; Patel, Mitali P.; Rogers, Andrew V.; Onoufriadis, Alexandros; Scully, Juliet; Daudvohra, Farheen; Cullup, Thomas; Loebinger, Michael R.; Wilson, Robert; et al.
In primary ciliary dyskinesia (PCD), motile ciliary dysfunction arises from ciliary defects usually confirmed by transmission electron microscopy (TEM). In 30% of patients, such as those with DNAH11 mutations, apparently normal ultrastructure makes diagnosis difficult. Genetic analysis supports diagnosis, but may not identify definitive causal variants. Electron tomography, an extension of TEM, produces three-dimensional ultrastructural ciliary models with superior resolution to TEM. Our hypothesis is that tomography using existing patient samples will enable visualisation of DNAH11- associated ultrastructural defects. Dual axis tomograms from araldite-embedded nasal cilia were collected in 13 PCD patients with normal ultrastructure ( DNAH11 n=7, HYDIN n=2, CCDC65 n=3 and DRC1 n=1) and six healthy controls, then analysed using IMOD and Chimera software. DNAH11 protein is localised to the proximal ciliary region. Within this region, electron tomography indicated a deficiency of >25% of proximal outer dynein arm volume in all patients with DNAH11 mutations (n=7) compared to other patients with PCD and normal ultrastructure (n=6) and healthy controls (n=6). DNAH11 mutations cause a shared abnormality in ciliary ultrastructure previously undetectable by TEM. Advantageously, electron tomography can be used on existing diagnostic samples and establishes a structural abnormality where ultrastructural studies were previously normal. 3D electron tomography identifies a defect in the cilia of patients with PCD and "normal ultrastructure" http://ow.ly/lZqd30hdPXM